Physicochemical properties and dentin bond strength of a tricalcium silicate-based retrograde material - de Paula Telles Pires Lucas, Camila [UNESP]; Viapiana, Raqueli [UNESP]; Bosso-Martelo, Roberta [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP]; Camilleri, Josette; Tanomaru-Filho, Mário [UNESP] (FapUNIFESP (SciELO), 2017)
The aim of this study was to evaluate the physicochemical properties and the apical dentin bond strength of the tricalcium silicate-based Biodentine in comparison to white MTA and zinc oxide eugenol-based cement (ZOE). Setting time and radiopacity were evaluated according to ISO 6876:2012 specification. Final setting time, compressive strength and pH were also assessed. Material’s bond strength to the apical root canal dentin was measured by the push-out assay. Data were analyzed by ANOVA and Tukey-Krammer post-hoc test. Biodentine presented the shortest initial (16.2±1.48 min) and final setting time (35.4±5.55 min). Radiopacity of Biodentine (2.79±0.27 mmAl) does not agree with ISO 6876:2012 specifications. On the other hand, Biodentine showed higher compressive strength after 21 days (37.22±5.27 MPa) and higher dentin bond strength (11.2±2.16 MPa) in comparison to white MTA (27.68±3.56 MPa for compressive strength and 2.98±0.64 MPa for bond strength) (p<0.05). Both MTA and Biodentine produced an alkaline environment (approximately pH 10) (p>0.05) compared to ZOE (pH 7). It may be concluded that Biodentine exhibited faster setting, higher long-term compressive strength and bond strength to the apical dentin than MTA and ZOE.
Keywords: Dentin bond strength; Mineral trioxide aggregate; Physicochemical properties; Tricalcium silicate